2020
DOI: 10.29145//jmr/71/070106
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Environmental Management Accounting and Control System between Top Management Commitment and Environmental Performance: A Legitimacy Theory

Abstract: The purpose of current study is to assess the impact of top management commitment on firms’ performance, based on legitimacy theory with mediating role of environmental management accounting and environmental management control system. Survey-based data has been collected through questionnaires from ISO 14001 based manufacturing firms of Pakistan. Path analysis has been conducted by applying structural equation modelling on total 304 respondents' data to answer the study hypotheses by using SPSS and AMOS. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
(56 reference statements)
1
10
0
Order By: Relevance
“…Hence, firms play their role in resolving social matters and getting financial success by creating a compelling value chain, publicprivate joint venture, and managing resources of the environment competently (Carroll, 2003;Kiran, 2015;Khattak & Saiti, 2021). Owing to worldwide environmental transformation and ecological corrosion, surroundings get affected (Amir, Rehman, & Khan, 2020). To get good performance, CER forces organizations to adopt those measures that can protect and improve surrounding and refer them to take responsibility for their environmental protection (Flammer, 2013;Holtbrügge, 2012;Kim & Park, 2021).…”
Section: Corporate Environmental Responsibility and Its Effect On Financialmentioning
confidence: 99%
“…Hence, firms play their role in resolving social matters and getting financial success by creating a compelling value chain, publicprivate joint venture, and managing resources of the environment competently (Carroll, 2003;Kiran, 2015;Khattak & Saiti, 2021). Owing to worldwide environmental transformation and ecological corrosion, surroundings get affected (Amir, Rehman, & Khan, 2020). To get good performance, CER forces organizations to adopt those measures that can protect and improve surrounding and refer them to take responsibility for their environmental protection (Flammer, 2013;Holtbrügge, 2012;Kim & Park, 2021).…”
Section: Corporate Environmental Responsibility and Its Effect On Financialmentioning
confidence: 99%
“…It means that IPs can push the organization to adopt and implement effective environmental systems and practices including EMA. For instance, political influence, laws, organizational authority, and policies may pressurize the organization to implement those practices for their EP (Amir, Rehman, & Khan, 2020; Betts et al, 2018). Similarly, an organization may adopt and apply EMA system because the other players are following and adopting EMA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Phan et al (2017) also revealed that EMAS implementation has a significant impact on a company's environmental performance. A study was done by Amir, Rehman, and Khan (2020) also found that EMAS adoption significantly mediates the relationship between top management commitment and environmental performance in Pakistan. Runlei, Jaidi, and Fatah (2020) also found that top management's commitment positively affects EMAS adoption and improvement in corporate sustainability performance among Malaysian manufacturing companies.…”
Section: Emas Adoption and Value Creationmentioning
confidence: 92%